Biofilm Formation and Antimicrobial Susceptibility Pattern of Staphylococcus aureus Clinical Isolates from Two Healthcare Facilities in Zaria (Nigerian Journal of Pharmaceutical Research, 2023)
Background: Antibiotic resistance is a public health challenge worldwide. There is a huge global concern about the increased drug-resistant S. aureus and the development of multiple resistance to several drugs. A well-designed surveillance study has been found to be a fundamental approach in the control of antimicrobial resistance.Objective: This study investigated the biofilm formation and antimicrobial susceptibility pattern of Staphylococcus aureus from two healthcare facilities in Zaria.Methods: A total of 200 presumptive Staphylococcal isolates from clinical specimens were collected and identified by conventional methods. Staphylococcus aureus isolates were tested against a panel of antibiotics using the modified Kirby-Bauer disk diffusion method, Methicillin-resistant Staphylococcus aureus (MRSA) were tested using cefoxitin disk, and Micro broth dilution method for Vancomycin Minimum Inhibitory Concentration (MIC). The biofilm-forming ability of the isolates were analyzed quantitatively using the microtitre plate method.Results: Of the 200 presumptive staphylococcal isolates, 22(11%) were Staphylococcus aureus. The antibiotic resistance pattern of the isolates shows high resistance to tigecycline (100%), vancomycin (100%), clindamycin (40.9%), and tetracycline (40.9). The occurrence of MRSA in this study was 18.8% and MDR (was 68.2%). The biofilm-forming ability of the Staphylococcus aureus isolates is; weak biofilm formers 16 (72.7%), moderate biofilm formers 5 (22.7%), and strong biofilm former 1 (4.5%).Conclusion: There is need for more research to ascertain the relationship between biofilm formation and antimicrobial resistance in Staphylococcus aureus. Close monitoring of antimicrobial resistance is necessary as it helps to design tangible actions that will yield the greatest impact to control the spread of resistant organisms.